La literatura digital en el sistema literario tradicional: el uso subversivo de los lenguajes en el ciberespacio - Gómez, Verónica Paula (2024)
E-literature is defined as “born digital”, this is, “a first-generation digital object created on a computer and (usually)meant to be read in a computer” (Hayles 2008: xiii). It is also experimental and its literary aspect is at first place,fulfilling what Jakobson (1973) called a “poetic function”. Due to the characteristics of the object, many e-literature works take more than one natural (national) language as well as other non-verbal languages such as musical,kinetic, visual to play with it in a subversive way. Whereas the traditional literature system relates to differentnational print languages following the modern way of framing national literatures, electronic literature is using software tools to transform what is written into something else, a fact that is usually out of consideration in the hegemonic field. E-literature pushes the “frontiers of [what is] possible” (Taylor 2017) causing tensions (Bouchardon 2018) inside and outside the traditional literature system. These tensions are not easy to solve because they involve languages, politics, and heterogeneous material resources playing in the virtual (cyber)space.